Pemberdayaan Masyarakat Melalui Kegiatan Pembagian Bantuan Pangan Oleh Mahasiswa MBKM Non-KKNT UPN Veteran Jawa Timur Bersama PT. Pos Indonesia Di Kota Surabaya - Alya Daywa Yudistira; Fani Khoirotunnisa (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
The improvement of public welfare becomes the benchmark for the success of a government role. Responding to this, the Indonesian government has taken various steps to improve public welfare, one of which is through the National Food Assistance Distribution Program (BPPN). This program aims to provide food assistance equitably to people in need, especially those below the poverty line.Together with UPNVJT Non-KKNT MBKM students, PT. Pos Indonesia through the Regional Post Office V Surabaya promotes the National Food Assistance Distribution Program (BPPN) to support the government's efforts to equalize public welfare, especially in Surabaya as a form of community service activities. Supported by the BAST Recapitulation process as a form of monitoring and evaluation of the National Food Assistance Distribution Program (BPPN) that has been implemented. In general, this community service activity shows that BPPN is an effective effort to improve public welfare. However, there needs to be evaluation and improvement in the implementation of this program in order to have a more optimal impact.